2021
DOI: 10.1002/bem.22325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temperature Increase From Joule Heat in Numerical Tooth Model by Applying 500 kHz Current for Apical Periodontitis Treatment—Effect of Applied Voltage and Tooth Conductivity

Abstract: For apical periodontitis treatments, a new method with the insertion of an electrode into the root canal of a tooth and application of a current at 500 kHz to sterilize the area by Joule heat has attracted attention. However, few studies have quantified the temperature increase in the root canal. This study aimed to investigate the basic characteristics of the temperature increase in a simple and standard tooth model when energizing a current at 500 kHz to the numerical tooth model with typical electrical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, during electrical conduction to the root canal, the higher impedance at the apical constriction and in accessory canals where the root canal is narrower means that the thermal energy increases in accordance with Ohm’s law and Joule’s law [ 39 ], generating Joule heat that may result in a large temperature increase. In a numerical simulation, Tarao et al [ 40 ] found that passing a 500 kHz, 60 V electric current through a root canal with an apical foramen 0.4 mm in diameter resulted in a 62 °C increase in the vicinity of the apical foramen after 0.1 s. Accordingly, when apical patency fails because of a ledge, step, or other obstruction, and the uninstrumented root canal is narrow, the current density of a high-frequency electric current increases, and Joule heat is generated, which may make it possible to cauterize the pathogenic factors in the root canal. However, all previous studies of the application of a high-frequency electric current in root canal treatment have used it to heat the tip of the file, and none have investigated its effect at the apical constriction where the temperature increase is the greatest.…”
Section: Introductionmentioning
confidence: 99%
“…However, during electrical conduction to the root canal, the higher impedance at the apical constriction and in accessory canals where the root canal is narrower means that the thermal energy increases in accordance with Ohm’s law and Joule’s law [ 39 ], generating Joule heat that may result in a large temperature increase. In a numerical simulation, Tarao et al [ 40 ] found that passing a 500 kHz, 60 V electric current through a root canal with an apical foramen 0.4 mm in diameter resulted in a 62 °C increase in the vicinity of the apical foramen after 0.1 s. Accordingly, when apical patency fails because of a ledge, step, or other obstruction, and the uninstrumented root canal is narrow, the current density of a high-frequency electric current increases, and Joule heat is generated, which may make it possible to cauterize the pathogenic factors in the root canal. However, all previous studies of the application of a high-frequency electric current in root canal treatment have used it to heat the tip of the file, and none have investigated its effect at the apical constriction where the temperature increase is the greatest.…”
Section: Introductionmentioning
confidence: 99%